2020
DOI: 10.3389/fpls.2020.00989
|View full text |Cite
|
Sign up to set email alerts
|

Failure of Pollen Attachment to the Stigma Triggers Elongation of Stigmatic Papillae in Arabidopsis thaliana

Abstract: Pollination is one of key determinants of yield production in important crops, such as grains and beans in which seeds are utilized as agricultural products. Thus, to fulfil food demand for growing world population, it is necessary to elucidate the mechanisms that regulate pollination, leading to increase in yield production. In this study, we compared detailed morphological characteristics of reproductive organs in Arabidopsis thaliana grown under control conditions or subjected to heat stress. Shorter length… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
13
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 22 publications
(13 citation statements)
references
References 48 publications
(81 reference statements)
0
13
0
Order By: Relevance
“…ROS also regulates root hair cell expansion, pollen tube growth, defense against pathogens, and initiates immune responses to abiotic stresses such as heat stress [ 53 , 54 ]. For tip growth and cell expansion, ROS accumulation (i.e., H 2 O 2 , O 2 − , lipid peroxides) due to heat stress plays a dual role depending on the type of tissue and organ and the cellular ROS threshold regulated by antioxidants such as glutathione (GSH), ascorbic acid (AsA), and flavonols [ 55 , 56 , 57 ]. For example, in Arabidopsis, ROS accumulation due to heat stress caused ferrotopsis-like regulated apoptosis (RCD) only in root cells (i.e., root hairs).…”
Section: The Role Of Ros In Plant Development and Its Relationshipmentioning
confidence: 99%
See 1 more Smart Citation
“…ROS also regulates root hair cell expansion, pollen tube growth, defense against pathogens, and initiates immune responses to abiotic stresses such as heat stress [ 53 , 54 ]. For tip growth and cell expansion, ROS accumulation (i.e., H 2 O 2 , O 2 − , lipid peroxides) due to heat stress plays a dual role depending on the type of tissue and organ and the cellular ROS threshold regulated by antioxidants such as glutathione (GSH), ascorbic acid (AsA), and flavonols [ 55 , 56 , 57 ]. For example, in Arabidopsis, ROS accumulation due to heat stress caused ferrotopsis-like regulated apoptosis (RCD) only in root cells (i.e., root hairs).…”
Section: The Role Of Ros In Plant Development and Its Relationshipmentioning
confidence: 99%
“…It has been reported that heat stress applied to Arabidopsis during reproductive organ development and pollination inhibits reproductive organs’ growth, such as the stamen. However, in the stigmatic papillae, O 2 − accumulation occurs due to heat stress, thereby promoting cell elongation [ 56 ]. The cell elongation caused by increased ROS in the papillae increases the distance between the stamens and the papillae under heat stress, which harms the efficiency of fertilization.…”
Section: The Role Of Ros In Plant Development and Its Relationshipmentioning
confidence: 99%
“…Several studies revealed the detailed dynamics of ROS and NO accumulation in reproductive organs [ 13 , 18 , 72 , 73 ]. Prior to the landing of pollens on the stigma, high level of NO and H 2 O 2 accumulate in pollens and papilla cells, respectively.…”
Section: Pollen Adhesion and Hydrationmentioning
confidence: 99%
“…Deficiency in these ROS scavenging enzymes resulted in the impairment of reproductive development [ 9 , 10 , 11 ]. In addition, observations of ROS accumulation in reproductive organs of various plant species demonstrated that ROS distribution altered depending on the stages of reproductive development [ 12 , 13 , 14 ]. These findings suggest that temporal-spatial patterns of ROS accumulation need to be strictly modulated for the proper reproductive development.…”
Section: Introductionmentioning
confidence: 99%
“…Pollen development is highly sensitive to abiotic stresses, such as heat, with exposure to elevated temperatures resulting in pollen cell death, male sterility, and a decrease in attachment to the stigma ( Barnabás et al, 2008 ; Hedhly et al, 2009 ; Zinn et al, 2010 ; Katano et al, 2020 ). Pollen heat sensitivity is related to the increased demand for metabolic energy, and cell wall precursor and protein synthesis during the short phase of microspore formation and maturation into pollen grains ( Lohani et al, 2019 ).…”
Section: Introductionmentioning
confidence: 99%